THE INFLUENCE OF GROWTH REGULATORS ON THE YIELD AND BIOCHEMICAL COMPOSITION OF LETTUCE (LACTUCA SATIVA L. VAR. SECALINA ALEF.) - Dydiv О.; Sobotovych М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Among the green (leafy) vegetable crops, lettuce (Lactuca sativa L.) occupies an important place. It has a short vegetation period and produces high-vitamin marketable products within 25-35 days. As a result, it can be grown and harvested three to six times during the spring, summer and autumn periods. Over the past three years, since the Russian-Ukrainian war began, there has been a downward trend in the public sector of vegetable growing and an upward trend in the private sector. It is noted that the application of plant growth regulators (PGR) is one of the effective means in terms of ecology to increase the yield and improve the quality of commercial products of lettuce as they are easily absorbed by plants. The effect on the yield and biochemical composition of lettuce was studied in the conditions of the Western Forest-Steppe of Ukraine on dark grey podzolic light loamy soils. The subject of the study was a variety of lettuce of domestic selection - Dublianskyi. The experimental scheme included the following options: 1) Control (water treatment); 2) Aminostar; 3) Humifield Forte; 4) Rival; 5) Humifriend. It was found that, on average, over two years, a large mass of leaf rosettes (210 and 268 g) was obtained in the variant where the growth regulators Rival and Humifriend were applied, while in the control (water treatment) this figure was the lowest and amounted to 150 g. With the seedling method of growing lettuce using plant growth regulators Rival and Humifriend, a high yield of marketable products (21.34 and 22.8 t/ha) was obtained, which exceeded the control (water treatment) by 4.24 and 5.7 t/ha, respectively. It was proved that plant growth regulators improve the quality of marketable lettuce products. In particular, the high content of soluble solids (8.60 and 8.90 %), dry matter (5.74 and 5.88 %), total sugar (1.38 and 1.56 %), vitamin C (5.24 and 6.58 mg/%), carotene (3.96 and 65 %) was provided by the variants with the introduction of growth regulators Rival and Humifriend. In all variants of the experiment, the nitrate nitrogen content did not exceed the maximum permissible concentration (1500 mg/kg). Thus, to obtain a high yield (21.34 and 22.86 t/ha) with good quality of marketable products of lettuce of Dublianskyi variety under the seedling method of cultivation on dark grey podzolic soils of the Western Forest-Steppe of Ukraine, it is advisable to use foliar application of growth regulators Rival and Humifriend.